Experimental studies on ovarian implementing some transplantable tumors of rats - Mori Chávez, Pablo (2015)
In an earlier publication on rat ovarian carcinoma he showed his predilection for implementing the ovary when it was transplanted intrsperitonealmente. The experiments referred to here extend work and show that three other tumors, in addition to ovarian carcinoma, were able to implant and grow in the ovaries. It has been considered and discussed the increased incidence of ovarian ovarian carcinoma implants in the intraperitoneal transplantation, concluding that this skill came from the most malignant and increased release of living cells capable of crossing the ostium of periovárico sack. It also showed that tumor cells were particularly favorable for growth in ovarian tissues, mainly in the corpora lutea medium.